Contrasting effects of viscous and particulate fibers on colonic fermentation in vitro and in vivo, and their impact on intestinal water studied by MRI in a randomized trial. Issue 3 (3rd July 2020) - Gunn, David; Murthy, Rajani; Major, Giles; Wilkinson-Smith, Victoria; Hoad, Caroline; Marciani, Luca; Remes-Troche, Jose; Gill, Samantha; Rossi, Megan; Harris, Hannah; Ahn-Jarvis, Jennifer; Warren, Fred; et al.
ABSTRACT: Background: Wheat bran, nopal, and psyllium are examples of particulate, viscous and particulate, and viscous fibers, respectively, with laxative properties yet contrasting fermentability. Objectives: We assessed the fermentability of these fibers in vitro and their effects on intestinal function relevant to laxation in vivo using MRI. Methods: Each fiber was predigested prior to measuring gas production in vitro during 48-h anaerobic incubation with healthy fecal samples. We performed a randomized, 3-way crossover trial in 14 healthy volunteers who ingested 7.5 g fiber twice on the day prior to study initiation and once with the study test meal. Serial MRI scans obtained after fasting and hourly for 4 h following meal ingestion were used to assess small bowel water content (SBWC), colonic volumes, and T1 of the ascending colon (T1AC) as measures of colonic water. Breath samples for hydrogen analysis were obtained while patients were in the fasted state and every 30 min for 4 h following meal ingestion Results: In vitro, the onset of gas production was significantly delayed with psyllium (mean ± SD: 14 ± 5 h) compared with wheat bran (6 ± 2 h, P  = 0.003) and was associated with a smaller total gas volume ( P  = 0.01). Prefeeding all 3 fibers for 24 h was associated with an increased fasting T1AC (>75% of values >90th centile of the normal range). There was a further rise during the 4 h after psyllium (0.3 ± 0.3 s P  = 0.009), a fall with wheat bran (−0.2 ± 0.2 s; P  = 0.02), but no change with nopal (0.0 ± 0.1 s, P  = 0.2). SBWC increased for all fibers; nopal stimulated more water than wheat bran [AUC mean (95% CI) difference: 7.1 (0.6, 13.8) L/min, P  = 0.03]. Breath hydrogen rose significantly after wheat bran and nopal but not after psyllium ( P  < 0.0001). Conclusion: Both viscous and particulate fibers are equally effective at increasing colonic T1 over a period of 24 h. Mechanisms include water trapping in the small bowel by viscous fibers and delivery of substrates to the colonic microbiota by more fermentable particulate fiber. This trial was registered at clinicaltrials.gov as NCT03263065.